Investment in Human Capital Among Administrative Staff : Case Study of Universiti Utara Malaysia - Ambigah, Sandran (2011)
This study examines trends in participation among administrative staff of Universiti Utara Malaysia on investment in human capital. The sample was collected using self-administered questionnaire which collected 100 respondents. The respondent rates are 50% men and 50% women for the admin staff of UUM. The result shows that 15% of the respondents do the investment in human capital. However , relatively the women participation in higher education is higher than the men involvements. Result of regression analysis shows that the investment in human capital relationship with the leisure time is important determination for the decision of investing in human capital. However, comparatively, the significant determination of investment in human capital are varies. One of most important determinants is the income of the respondent with the negative relationship. Another determinants with negative relationship when investing in human capital is the time for caring the children and the time spend to teach other for educational. Other determinants include time spends on watch programs or movies consider as a positive relationship during the decision of investing in human capital. The implication of policy and suggestion are discussed on increase the number of participation on investment in human capital in Universiti Utara Malaysia.